Survei Minat dan Motivasi Siswa Tunagrahita Dalam Pembelajaran Pendidikan Jasmani Di SDLB Negeri Kots Tegal Tahun 2019 (Indonesian Journal for Physical Education and Sport, 2020)
The problem in this research is how much interest and motivation students in physical education learning in SDLB Negeri Tegal 2019. The purpose of this research is to find out how big the interests and motivations of students with intellectual disabilities to follow learning physical education at SDLB Negeri Tegal in 2019. This research is a quantitative descriptive study using survey method. The sampling technique uses a total technique sampling. Data collection using a questionnaire, observation, documentation, and unstructured interviews. Data analysis uses statistics descriptive percentage. Based on the results of the study it can be concluded that the interests of students with special needs for mental retardation at SDLB Negeri Tegal in participating physical education learning in schools the average student interest is at medium category which is 64%. Survey of students' mental retardation motivation in physical education learning shows the average motivation of students are in the medium category which is 68%. Then it is suggested to the teacher that further enhance creative and innovative learning, so that students are more active in moving, so learning is going on can be effective in students and increase student interest and motivation in participating in physical education learning.